Global Collaborations for Cervical Cancer: Can the East–West Alliance Facilitate Treatment for all?. Issue 8 (August 2019) - Chopra, S.; Mittal, P.; Viswanathan, A.; Tharavichitkul, E.; Zubizarreta, E.; Nout, R.A.; Yap, M.L.; Grover, S.; Rodin, D.; Rai, B.; Gondhowiardjo, S.; Shrivastava, S.K.
Abstract: Despite the advances in the primary prevention of cervical cancer, there is an absolute increase in the incidence of cervical cancer as a result of an increase in world population. A vast majority of patients in low and low–middle income countries continue to present at a locally advanced stage, necessitating treatment with chemoradiation and brachytherapy. There is a dearth of equipment and trained professionals for the treatment of cervical cancer, especially in low and low–middle income countries. There is an urgent need to improve treatment availability and develop better treatments. Worldwide trends, however, reveal a low number of therapeutic and innovative research trials in cervical cancer. The present article elucidates the existing challenges and provides solutions to improve outcomes. The proposed strategies hinge on strengthening collaborations for global advocacy.